2022
DOI: 10.3389/fendo.2022.882906
|View full text |Cite
|
Sign up to set email alerts
|

Value of Immunohistochemical Expression of Apelin, Succinate Dehydrogenase B, Chromogranin B, Human Epidermal Growth Factor Receptor-2, Contactin 4, and Succinyl-CoA Synthetase Subunit Beta in Differentiating Metastatic From Non-Metastatic Pheochromocytoma and Paraganglioma

Abstract: ObjectiveWe aimed to retrospectively collect pathologically identified pheochromocytoma and paraganglioma (PPGL) tumor tissues from our center and investigate the expression of apelin and succinyl-CoA synthetase subunit beta (SUCLG2), human epidermal growth factor receptor-2 (HER2 or ERBB-2), contactin 4 (CNTN4), chromogranin B (CHGB), and succinate dehydrogenase B (SDHB) in metastatic and non-metastatic PPGLs, for exploring their roles in the diagnosis of metastatic PPGLs.MethodsA total of 369 patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Previous studies which performed SDHB IHC also showed that the loss of SDHB protein is associated with poor prognosis ( 30 , 32 ), and they discovered that patients with SDHB (-) tumors had considerably lower OS and DFS than those with SDHB (+) tumors. Compared to the research mentioned above, our study had a larger sample size and a longer follow-up time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies which performed SDHB IHC also showed that the loss of SDHB protein is associated with poor prognosis ( 30 , 32 ), and they discovered that patients with SDHB (-) tumors had considerably lower OS and DFS than those with SDHB (+) tumors. Compared to the research mentioned above, our study had a larger sample size and a longer follow-up time.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that SDHB protein loss can be used as an IHC biomarker to independently predict the prognosis of PCC/PGL patients ( 30 32 ), and a modified GAPP system (M-GAPP) and COPPs scoring system also incorporates loss of SDHB staining for analyzing PCC/PGL risk ( 18 , 33 ). Despite these above studies have included SDHB IHC in the investigation of the prognosis of PCC/PGL, no reliable prospective study or long-term follow-up for PCC/PGL focusing on SDHB IHC is available at present.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that CNTN4 has been found overexpressed at the mRNA level in malignant PCPG comparing with benign 15 . However, there is no significant difference in protein expression of CNTN4 between benign and malignant PCPG in immunohistochemistry 16 . The abnormal expression of SH3GL2 is mainly related to the pathogenesis of Parkinson's disease, as well as the migration and invasion behaviors of glioblastoma and triple‐negative breast cancer 17–19 .…”
Section: Discussionmentioning
confidence: 96%
“…15 However, there is no significant difference in protein expression of CNTN4 between benign and malignant PCPG in immunohistochemistry. 16 The abnormal expression of SH3GL2 is mainly related to the pathogenesis of Parkinson's disease, as well as the migration and invasion behaviors of glioblastoma and triple-negative breast cancer. [17][18][19] In the present study, the expression of…”
Section: Identification Of the Prognostic Markersmentioning
confidence: 99%
“…The expression of human telomerase reverse transcriptase (hTERT) and heat shock protein 90 (HSP90) is higher in metastatic tumors [ 58 ]. Other markers such as chromogranin B and S100 protein have been associated with nonmetastatic tumor behavior [ 23 , 38 , 59-63 ].…”
mentioning
confidence: 99%